2004
DOI: 10.4049/jimmunol.173.12.7324
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Myeloid Suppressor Cells in SHIP-Deficient Mice Represses Allogeneic T Cell Responses

Abstract: Previously we demonstrated that SHIP−/− mice accept allogeneic bone marrow transplants (BMT) without significant acute graft-vs-host disease (GvHD). In this study we show that SHIP−/− splenocytes and lymph node cells are poor stimulators of allogeneic T cell responses that cause GvHD. Intriguingly, SHIP−/− splenocytes prime naive T cell responses to peptide epitopes, but, conversely, are partially impaired for priming T cell responses to whole Ag. However, dendritic cells (DC) purified from SHIP−/− splenocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
108
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 33 publications
15
108
1
Order By: Relevance
“…Hemopoietic stem cells in SHIP Ϫ/Ϫ mice exhibit spontaneous mobilization and reduced BM retention that may reduce the competitive barrier to engraftment by donor hemopoietic stem cells in SHIP-deficient BMT recipients (17). Furthermore, GVHD is reduced in SHIP Ϫ/Ϫ BMT recipients (15) due to a profound expansion of immunoregulatory MySC in secondary lymphoid tissues (7). Although this confluence of genetic abnormalities may contribute to the reduced viability of germline SHIP Ϫ/Ϫ mice (7,22), these studies led us to propose that induction of SHIP deficiency for a short period before allogeneic BMT might enhance engraftment and survival even in settings in which donor and host have a complete MHC mismatch (7,15).…”
Section: G Raft-vs-host Disease (Gvhd)mentioning
confidence: 99%
See 3 more Smart Citations
“…Hemopoietic stem cells in SHIP Ϫ/Ϫ mice exhibit spontaneous mobilization and reduced BM retention that may reduce the competitive barrier to engraftment by donor hemopoietic stem cells in SHIP-deficient BMT recipients (17). Furthermore, GVHD is reduced in SHIP Ϫ/Ϫ BMT recipients (15) due to a profound expansion of immunoregulatory MySC in secondary lymphoid tissues (7). Although this confluence of genetic abnormalities may contribute to the reduced viability of germline SHIP Ϫ/Ϫ mice (7,22), these studies led us to propose that induction of SHIP deficiency for a short period before allogeneic BMT might enhance engraftment and survival even in settings in which donor and host have a complete MHC mismatch (7,15).…”
Section: G Raft-vs-host Disease (Gvhd)mentioning
confidence: 99%
“…SHIP's role in signal transduction allows it to regulate cell survival, proliferation, apoptosis, and homeostasis of certain hemopoietic cell types (7,(13)(14)(15)(16), as well as primitive stem cell populations (11,12,17,18). Analysis of SHIP-deficient mice revealed that this protein also has a prominent role in the immune system (7,14,15,19). Significant pathologies have been observed in SHIP Ϫ/Ϫ mice, including splenomegaly and an infiltration of myeloid cells into the lungs that contributes to their reduced life span (13,16,20).…”
Section: G Raft-vs-host Disease (Gvhd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although in the allogeneic setting regulatory T cell (Treg) accumulation triggered by myeloid Gr1 ϩ CD11b ϩ suppressor cells (MSC) reduces acute graft-versus-host disease (GVHD) 1 but instead worsens chronic GVHD, 2 in autoimmune diseases the expansion of Treg is expected to be beneficial. In the experimental model of spontaneous autoimmune diabetes in nonobese diabetic (NOD) mice, we have recently demonstrated 3 that Lin Ϫ Sca1 hi ckit hi Flt3 ϩ CD34 ϩ CD106 ϩ CD127 Ϫ multipotent hematopoietic progenitor cells (HPCs) mobilized to the spleen by a combination of granulocytecolony stimulating factor (G-CSF) and FMS-like tyrosine kinase 3 ligand (Flt3L), have a tolerogenic potential and that their transplantation halts autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 99%